MENINGKATKAN KINERJA BISNIS MELALUI KEUNGGULAN BERSAING KULINER KHAS SEMARANG (StudiPada Sentra Usaha MikroLumpia, Bandeng Presto danWingko di Kota Semarang) - Bogy Febriatmoko; Susilo Toto Raharjo (Conference In Business, Accounting, And Management (CBAM), 2015)
This research analyze the effect of entrepreneurship orientation, market orientation, and competitive advantage to enhance the business performance. This research formula is how to create competitive advantage to enhance the business performance. The population which has selected in this research is micro business cluster of lumpia, bandeng presto, and wingko in Semarang. Those are 104 industries and total sample of this research are 102 industries. Collecting data using questionnaire with score start from 1 (very disagree at all) to 7 (strongly agree at all). The data analysis tool which used is Structural Equation Modelling (SEM) with AMOS 18. The result of the data analysis goodness of fit index shows that the research model has the suitability of fit (acceptable). Not all hypothesis can be accepted after SEM analysis. Accepted hypothesis is the effect of entrepreneurship orientation on business performance, market orientation on competitive advantage, and competitive advantage on business performance. While the rejected hypothesis is the effect of entrepreneurship orientation on competitive advantage and market orientation on business performance. Generally, the conclusion from the result of testing model which applied to micro business cluster of lumpia, bandeng presto, and wingko in Semarang shows that competitive advantage can be achieved through market orientation, where competitive advantage which resulted by the firm can enhance the business performance. This research provides some research limitation and future research agenda that can be done to further research. Keywords: entrepreneurship orientation, market orientation, competitive advantage, business performance